What Indonesian EFL Learners Perceive of Collaborative Writing: Experience in Writing Essays Online - Risa Fitria; Ika Kana Trisnawati; Mulyani Mulyani (English Education Journal, 2023)
This study examines online collaborative writing (CW) teaching techniques via asynchronous computer-mediated communication multimodality, i.e., Google Docs. This study attempts to investigate what Indonesian learners perceive concerning writing collaboratively in Google Docs during online learning. This study collected data from 20 Primary School Teacher Education (PSTE) students enrolling in an English 3 (Academic Writing) class at a private university in Indonesia. The findings showed that the participants perceived online collaborative writing as a good way to develop their writing and communication skills. It was found that feedback from peers and the teacher was considered beneficial to the learners’ writing development during the implementation of online collaborative writing (OCW). Even though interaction among learners can be enhanced in OCW, learners’ lack of participation was one of the drawbacks discovered in this study. It is hoped that this study can contribute significantly to English writing instructors considering the benefits and the drawbacks of OCW before implementing OCW in their university classrooms.